Occupational stressors among women bus drivers in the public transport sector - Maswikeni, Ananciata (My University, 2020)
This study explores the occupational stressors among women bus drivers in the public sector. The physical and psychological health of public transport bus drivers and the occupational stressors they experience are critical factors in driving performance as any impairment could lead to adverse consequences for both the driver and the passengers. It is particularly important to study occupational stress among women bus drivers, as the occupation is a recent phenomenon for women in contemporary South Africa and has become more popular with the advent of government policies that promote gender equality and have seen more women engaging in nontraditional jobs such as bus driving. This research employed qualitative research techniques and the units of analysis were women bus drivers employed by one of the largest bus companies in South Africa. The semi structured interview schedule was used as the primary data collection instrument and in-depth face-to-face interviews were used to gather data. Two separate semi-structured interview schedules, one for women bus drivers and the other one for managers, were constructed to collect data that were analysed using a six-phase guide to thematic content analysis. The research findings revealed that women bus drivers were faced with numerous occupational stressors which can be grouped into physical and psychological stressors. The findings also revealed that apart from very limited services offered by the company to reduce occupational stress, women bus drivers have developed their own coping mechanisms in order to survive the stressful situations. It emerged that although the company has programmes in place to deal with occupational stress, it appears that these interventions by the company were not sufficient to deal with occupational stress and its effects in the workplace. The main recommendation emanating from the study is that there is a need for transformation in internal policy reforms towards supporting employees in dealing with occupational stress. It is hoped that the findings of this study may contribute to the knowledge base of occupational stressors affecting South African bus drivers. Moreover, the study has the potential of being beneficial to the bus company as it is likely to provide information on the occupational stressors of their women bus drivers that may be useful in influencing company policy regarding employee wellbeing
A research report presented to the Department of Social Work School of Human and Community Development, Faculty of Humanities University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Arts in Occupational Social Work, 2020